Bazzania genus of Marchantiophyta in the Batang Toru Forest, North Sumatra, Indonesia - Damanik, Risjunardi; Pasaribu, Nursahara; Siregar, Etti Sartina; Syamsuardi, Syamsuardi (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
This study aims to enhance the existing knowledge on the diversity of liverworts within the genus Bazzania in Indonesia, specifically in North Sumatra, where such research is relatively limited. North Sumatra offers a rich habitat for liverworts, particularly within the Batang Toru forest, which experiences extremely high rainfall, resulting in optimal humidity for liverwort growth, including Bazzania species. The goal of this study is to contribute to the literature regarding Bazzania found in the Batang Toru forest. Sample collection involved exploring the hiking trails of the Batang Toru Forest as part of an exploration survey. Bazzania specimens were collected directly from leaves and cut from bark, rocks, or soil using a knife. All collected Bazzania liverworts were placed in designated dry specimen envelopes. This research successfully identified 13 Bazzania species, three of which are new records for Sumatra: Bazzania parabidentula, Bazzania parisii, and Bazzania scalaris. The most frequently collected specimens were Bazzania caudistipula, Bazzania calcarata, and Bazzania densa. The presence of Bazzania in the Batang Toru forest indicates that the area remains in a natural state. Consequently, this research aimed to inventory Bazzania in the Batang Toru forest and to enhance the understanding of Indonesia's natural wealth, particularly concerning Marchantiophyta.